Status of Anthelmintic Resistance against Gastrointestinal Nematodes in Small Ruminants of Bhiwani District (Haryana) - Priyanka; Vohra, Sukhdeep; Singh, Satyavir; Sangwan, Arun K. (International Journal of Livestock Research, 2019)
Sixty sheep and 60 goats of Bhiwani district, Haryana with eggs per gram of more than or equal to 150 were divided into four groups of 15 animals each. Group I, II and III were dosed with fenbendazole, morantel and ivermectin, respectively in sheep and double dose in goats. Group IV served as untreated control. Faecal egg count on day of treatment (0 day) and 12th day post treatment were determined by the modified McMaster technique. Results revealed that fenbendazole, morantel and ivermectin in sheep reduced the faecal egg counts by 100% indicating susceptibility. In goats, fenbendazole and ivermectin reduced the faecal egg count by 100% and 98.44%, respectively indicating susceptibility. Morantel caused 95.31% reduction with lower confidence levels 86.26% indicating suspected resistance. Thus, the present study revealed that fenbendazole, morantel and ivermectin were effective against gastrointestinal nematodes in sheep and goats of unorganized sector in Bhiwani district, Haryana.